Economies of scale in UK building societies: A re-appraisal using an entry/exit model - Drake, Leigh; Simper, Richard (Journal of Banking & Finance, 2002)
This study advances an entry/exit model to analyse the scale efficiency of UK building societies. We find that there are considerable divergences across building societies in levels of scale efficiency and also in technological change during the sample period 1992–1997. The paper also finds that scale economies and technological change estimates are dependent on whether the econometrician balances a panel data set or utilises the entry/exit model based on Dionne et al's (1998) specification. In general, scale economies in UK building societies are found to be more significant and more pervasive than in previous studies.